2014
DOI: 10.2147/opth.s67025
|View full text |Cite
|
Sign up to set email alerts
|

Navigated focal laser photocoagulation for central serous chorioretinopathy

Abstract: Background and objectiveTo assess the efficacy of navigated laser (Navilas®) treatment for central serous chorioretinopathy.Materials and methodsProspective study included 16 eyes of 15 subjects with nonresolving central serous chorioretinopathy. Fluorescein-angiography guided Navilas® treatment was performed. Pre- and posttreatment best-corrected visual acuity, pre- and posttreatment central macular thickness, number of leaks on fluorescein angiography, and various treatment parameters were analyzed. Pain exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
19
0
3
Order By: Relevance
“…Alternatively, the 810 or 577 nm subthreshold MP laser photostimulation employing low-intensity, high-density laser in a repetitive short pulses during 5-15% of duty cycle stimulate the production of intracellular antiangiogenic and restorative biological factors without causing visible laser scars with appreciable resorption of SRF [11,[29][30][31]. Other studies have shown that subthreshold laser energy induces local regenerative effects, such as restoration of the RPE blood retinal barrier and increased cell adhesion [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the 810 or 577 nm subthreshold MP laser photostimulation employing low-intensity, high-density laser in a repetitive short pulses during 5-15% of duty cycle stimulate the production of intracellular antiangiogenic and restorative biological factors without causing visible laser scars with appreciable resorption of SRF [11,[29][30][31]. Other studies have shown that subthreshold laser energy induces local regenerative effects, such as restoration of the RPE blood retinal barrier and increased cell adhesion [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, several treatment modalities for chronic CSCR have been investigated. These have included pharmacologic therapy, continuous-wave conventional laser thermal photocoagulation, photodynamic therapy (PDT), anti-vascular endothelial growth factor (anti-VEGF), and subthreshold micropulse diode laser [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Существуют работы, описывающие применение навигационной технологии (система NAVILAS) для лечения ЦСХ [5,6], однако они базируются на ФАГкартировании источника транссудации. Единственная работа описывает ОКТ-картирование в лечении ЦСХ, однако авторы использовали традиционную ЛК без навигационной технологии [7].…”
Section: Discussionunclassified
“…Навигационная модификация лазерной терапии, использованная в данном исследовании, ранее продемонстрировала свою эффективность и безопасность в лечении неразрешившейся ЦСХ [15,16]. При этом за счет навигационной технологии снижается вероятность ятрогенного поражения аваскулярной зоны.…”
Section: рис 6 навигационная фокальная лазерная коагуляция точки прunclassified
“…По данным J. Chhablani и соавторов, для навигационной коагуляции одной точки просачивания достаточно одного коагулята [16], что обеспечивает минимальное повреждение сетчатки. Однако в данном исследовании для коагуляции точки просачивания использовали более 1 лазерной аппликации (в среднем 3,1±0,5), так как отслойка ПЭС, которая была мишенью лазерного воздействия, больше соответствующей ей точки просачивания.…”
Section: рис 6 навигационная фокальная лазерная коагуляция точки прunclassified